PENGARUH TERPAAN MEDIA SOSIAL AKUN INSTAGRAM @ecommurz TERHADAP PEMBENTUKAN CITRA PADA PERUSAHAAN START-UP RUANGGURU - Syahrul Muhammad Elham (2022)
News on the exploitation of interns at the Ruangguru company on the @ecommurz Instagram account. The problem occurred, starting from internal stakeholders, namely interns at the Ruangguru company who gave testimonials about the exploitation they experienced at Ruangguru to the @ecommurz instagram account. The audience gave their opinions, arguments and responses to the Ruangguru company after they learned about the problem. The purpose of the study was to find out how much influence the social media exposure of the @ecommurz Instagram account had on the image formation of the Ruangguru startup company. The researcher uses the S-O-R theory as the basis. The method used in explanatory quantitative research with a positivist paradigm. Based on the results of research conducted, the value of t arithmetic (4.960) > t table (1.984), from the data above, it can be interpreted that H0 is rejected and H1 is accepted. The value obtained from the coefficient of determination or R (square) is 0.201. Based on the reality of the data above, it can be concluded that there is a significant influence between the exposure of social media to the Instagram account @ecommurz on image formation at the Ruangguru startup company by 20.1%.